PENDIDIKAN DAN PEMBELAJARAN BERORIENTASI PEMECAHAN MASALAH MASA DEPAN - Hety Mustika Ani (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2016)
The process ofeducation is an effort to prepare people to be able to live a decent future. Education should be a bridge for students to be able to deliver on the life of the present into the future life. Learners who are in school today are prepared to live a decent and useful both for themselves, their families and communities in the future. Through education are also expected to be grown the ability to cope with the demands of the present objective, both the demands of domestic and external demand due to the influence of society. Through education will be set measures been present as an effort to realize the aspirations and hopes of the future.Keywords: education, learning, future